Specification for ground investigation (Thomas Telford, 1993)
This Specification includes associated Schedules and a Bill of Quantities, and is intended for general application to ground investigation work. The Bill of Quantities is presented as a preamble and a comprehensive list of work items, which conveniently cross-relate to the Specification items.
Keywords: Soil mechanics.; elektronické knihy; electronic books